Cuneiform tablets from various auctions - Part II, The third dynasty of Ur - Theis, Christoffer (Nouvelles assyriologiques brèves et utilitaires, 2021)
The present article offers a compilation of inscribed clay tablets from various auctions and collections. It continues the first part, which contains material from the Third Millennium B.C. up to the beginning of the Third Dynasty of Ur. The aim of